Performansi Implementasi Numerik Metode Pseudo Spectral pada Model Gelombang 1D Boussinesq - Didit Adytia (Indonesia Journal on Computing (Indo-JC), 2017)
In the design of a numerical wave tank, it is necessary to use an accurate wave model as well as to choose an accurate and efficient numerical scheme for implementing the model. In this paper, we use a Pseudo-Spectral (PS) implementationfor a wave model so called Variational Boussinesq Model. The implementation is aimed to obtain a higher time efficiency in the calculation of wave simulations. The performance  of the PS implementation  is compared in CPU-time with a Finite Element (FE) implementation of the wave model for simulating a focusing wave group. Results of both implementations give a good agreement with wave data from laboratory experiment. The PS-implementation gives more efficient CPU-time compared to the FE-implementation.